Nutrient Adequacy of Global Food Production - Chen, Canxi; Chaudhary, Abhishek; Mathys, Alexander (Frontiers in Nutrition, 2021)
A major challenge for countries around the world is to provide a nutritionally adequate diet to their population with limited available resources. A comprehensive analysis that reflects the adequacy of domestic food production for meeting national nutritional needs in different countries is lacking. Here we combined national crop, livestock, aquaculture, and fishery production statistics for 191 countries with food composition databases and accounted for food loss and waste occurring at various stages to calculate the amounts of calories and 24 essential nutrients destined for human consumption. We then compared the domestic production quantities of all nutrients with their population-level requirements estimated from age- and sex-specific intake recommendations to assess the nutrient adequacy of the national food production. Our results show inadequate production of seven out of 25 nutrients (choline, calcium, polyunsaturated fatty acids, vitamin A, vitamin E, folate, and iron) in most countries, despite the overall adequacy of the total global production. High-income countries produce adequate amounts of dietary nutrients in general, while the foods produced in low-income countries mainly comprising roots and cereal products often lack in important micronutrients such as choline, calcium, and vitamin B12. South Asian food production barely fulfills half of the required vitamin A. Our study identifies target nutrients for each country whose domestic production should be encouraged for improving nutritional adequacy through interventions such as increasing the production of foods or fortified foods that are rich in these inadequate nutrients while not undermining the local environment. This assessment can serve as an evidence base for nutrition-sensitive policies facilitating the achievement of the Sustainable Development Goals of zero hunger and good health and well-being.